Advances in sphingolipidoses: CRISPR-Cas9 editing as an option for modelling and therapy - Amaral, Olga (2020)
We acknowledge the collaboration of Meg Quint in the proofreading of the manuscript and the team at the Unit of R&D of DGH at INSA-Porto for the agreeable environment provided.